Know how - Stanley, Jason (Oxford : Oxford University Press, 2011)
Jason Stanley presents a powerful account of how we acquire knowledge. He argues for the surprising thesis that practical knowledge is a kind of theoretical knowledge: that knowing how to do something amounts to knowing a truth about the world. It is our success as inquirers that explains our capacity for engagement with the world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of